2009
DOI: 10.1080/01926180802151919
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Remarried Families

Abstract: Assignment presented in partial fulfilment of the requirements for the degree of Master of Arts (Counselling Psychology) at the University of StellenboschSupervisor: Prof A P Greeff April2005Il STATEMENT I, the undersigned, hereby declare that the work contained in this assignment is my own original work and, that I have not previously in its entirety or in part submitted it at any university for a degree.Stellenbosch University http://scholar.sun.ac.za iii ABSTRACT Using a cross-sectional survey research desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 31 publications
4
43
0
3
Order By: Relevance
“…These results are supported by several studies that found a correlation between the identification by the adolescents of social support from family and friends and greater levels of well-being (Casas et al, 2007;Sarriera et al, 2012). Regarding family transitions, social support appraisals from friends may facilitate the emergence of adaptation processes if, for example, the adolescent is experiencing the separation and remarriage of parents (Greeff & Du Toit, 2009). In this sense, the friends would be a source of emotional support that encourages adolescents to share their experiences and feelings and to learn to address conflict.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…These results are supported by several studies that found a correlation between the identification by the adolescents of social support from family and friends and greater levels of well-being (Casas et al, 2007;Sarriera et al, 2012). Regarding family transitions, social support appraisals from friends may facilitate the emergence of adaptation processes if, for example, the adolescent is experiencing the separation and remarriage of parents (Greeff & Du Toit, 2009). In this sense, the friends would be a source of emotional support that encourages adolescents to share their experiences and feelings and to learn to address conflict.…”
Section: Discussionsupporting
confidence: 60%
“…Similar results have been found by other studies that observed that family configuration does not affect the well-being of children (Adler-Baeder et al, 2010;Fernandes, 2007). The results of this study suggest that the circumstances that the families are experiencing, whether normative or not, can be addressed throughout the life of individuals in a more or less competent manner (Greeff & Du Toit, 2009;Mota & Matos, 2011). Thus, the family transitions are not events that are associated with less adaptive pathways.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations